Wholesalers, wholesale markets, and symbiosis with the emerging logistics sector - Reardon, Thomas (International Food Policy Research Institute, 2024)
This paper is a summary review of empirical knowledge about wholesalers and wholesale markets in symbiosis with 3PLS (third party logistics) in developing regions and the implications for policy. The primary geographic focus is on developing and emerging market economies (Africa, Asia, Central and Eastern Europe, and Latin America), but also provides a comparison with the evidence regarding the evolution and roles 3PLS and wholesale markets in agrifood value chain development in the United States and Western Europe. Our review on this subject is timely given that the midstream segments of output value chains have been identified as an important theme about which there is inadequate research and policy debate (Barrett et al. 2022) despite their importance to consumers and farmers. A crucial segment of the midstream is the wholesale sector. Estimates are that much, if not most, produce is handled by wholesalers and wholesale markets in developing regions. Moreover, there has been growth and then transformation of the wholesale sector with urbanization and emerging modernization of retail as well as impacts of important public investments and regulatory policies. Finally, there remain important policy challenges and research gaps related to this topic that are an urgent agenda over the next decade – and beyond.